Achieving triple bottom line sustainability in supply chains: The role of environmental, social and risk assessment practices. Issue 2 (5th December 2018) - Miemczyk, Joe; Luzzini, Davide
Abstract : Purpose: Companies are increasingly challenged by sustainability-related supply chain risks. Research has developed linking supply chain sustainability priorities, practices and triple bottom line performance; however, risk is rarely included in these models. The purpose of this paper is to understand the link between sustainable supply chain strategies, practices and performance, and to test the importance of risk management practices in this relationship focusing on the product category level. Design/methodology/approach: The paper includes a survey of supply managers in four countries with 305 responses, with a focus on upstream supply chain strategies at the product category level. Findings: The environmental and social sustainability strategies lead to sustainable supply sustainable performance, through focused practices in either area, but the effect on operational and cost performance is not significant. Social supply chain strategies positively impact environmental and cost performance when mediated by risk assessment practices. Originality/value: This paper shows a more nuanced view of the impact of supply chain practices on the strategy–performance link. It is one of the first papers to empirically test the role of risk practices in sustainable supply chain management and emphasize the importance of alignment across the main dimensions of sustainability to achieve positive sustainable performance outcomes, but not necessarily cost and operational performance. Unlike other studies, social sustainability priorities may positively impact environmental and social performance and is linked to cost advantage when implemented with risk assessment practices.